2015
DOI: 10.5539/ass.v11n5p91
|View full text |Cite
|
Sign up to set email alerts
|

The Guidelines for Management of Community Enterprises: A Case Study of Don Chang Sub-district, Khon Kaen Province, Thailand

Abstract: The objectives of this study are to study the strengths, weaknesses, opportunities and threats facing community enterprises and to study the guidelines for management of community enterprises. In this study we used a qualitative method with in-depth interviews with 48 members of community enterprises, invited 15 people to participate in a focus group, and used content analysis and descriptive analysis to analyze the data. The results of this study found that community enterprises have several problems, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…In a CE, people set up their own business using the community’s resources and management skills. Among the main objectives of a CE are production, marketing and selling of locally produced goods at a more affordable price than big companies producing the same product (Somswasdi et al , 2015). Several types of CEs are present in Thailand, such as mushroom (Changwatchai and Santipolvut, 2015), textile (Distanont et al , 2017; Naipinit et al , 2016; Seenuankaew et al , 2018), curry paste (Seenuankaew et al , 2018), handicrafts, fishery, forestry and wood products (Naipinit et al , 2016) and rice (Cavite et al , 2021c; Prasertwattanakul and Ongkunaruk, 2015; Raungpaka and Savetpanuvong, 2017; Ruangsarakul et al , 2019; Seenuankaew et al , 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a CE, people set up their own business using the community’s resources and management skills. Among the main objectives of a CE are production, marketing and selling of locally produced goods at a more affordable price than big companies producing the same product (Somswasdi et al , 2015). Several types of CEs are present in Thailand, such as mushroom (Changwatchai and Santipolvut, 2015), textile (Distanont et al , 2017; Naipinit et al , 2016; Seenuankaew et al , 2018), curry paste (Seenuankaew et al , 2018), handicrafts, fishery, forestry and wood products (Naipinit et al , 2016) and rice (Cavite et al , 2021c; Prasertwattanakul and Ongkunaruk, 2015; Raungpaka and Savetpanuvong, 2017; Ruangsarakul et al , 2019; Seenuankaew et al , 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In spite of the support that RPCEs gained from various government and private initiatives, problems were still identified, affecting their production and marketing performance. For example, Somswasdi et al (2015) identified problems such as unattractive product designs and products that cannot compete in mass markets. In addition, Seenuankaew et al (2018) pinpointed drawbacks such as information needs and information seeking, which are important to strengthen CEs capacity towards the operational level.…”
Section: Review Of Literaturementioning
confidence: 99%
“…For knowledge distribution, therefore, the community enterprise should know how to acquire and transfer knowledge appropriately such as using processes of teaching, introduction, or demonstration [6]. This view is compatible with the guidelines for management of community enterprises proposed by Somswasdi and colleague [7], which found that community enterprises have several problems, such as internal management within their organization and a lack of knowledge of all aspects of management. For the development of community enterprises, a training program is important to improve their knowledge and skill.…”
Section: Introductionmentioning
confidence: 83%
“…Government agencies should be involved in the organization of training programs for community groups, so that they can acquire knowledge and increase their incomes. In particular, supporting low-interest funding sources, creating investment alliances and providing access to funding sources are essential to the management of community enterprises [25], [26]. Quality control is an important aspect that community enterprises should implement as a standard.…”
Section: The Concept Of Community Enterprisesmentioning
confidence: 99%